Development of Formative Tests Based on Self-Directed Learning-Oriented Assessment for Mathematics in Junior High School - Ihsanul Amin; Chairil Faif Pasani; Kamaliyah Kamaliyah; Zainudin Hassan (Journal of Mathematics Science and Computer Education, 2026)
Formative assessment practices in schools often focus on Assessment for Learning (AfL) but insufficiently facilitate Assessment as Learning (AaL), limiting students’ reflection and self-assessment. To address this, Self-directed Learning Oriented Assessment (SLOA) is employed as an approach integrating self-assessment to foster self-directed learning capacities by aligning the functions of assessment of, for, and as learning. This study aimed to develop valid, practical, and effective SLOA-based formative tests for junior high school mathematics. The study employed a research and development (R&D) approach using the ADDIE model. The research was conducted in a single seventh-grade class at a junior high school in Barito Kuala under the Kurikulum Merdeka, involving 25 students and one mathematics teacher. Data were collected through expert validation sheets, a teacher practicality questionnaire, and students’ mastery of learning outcomes. The results indicated that the developed formative tests and self-assessment sheets were very valid, with mean scores of 3.47 and 3.36, respectively. The product was categorized as very practical, obtaining a practicality percentage of 98%. In terms of effectiveness, the product was categorized as effective, with an average classical mastery reached of 61.3%, derived from three test packages showing a consistent upward trend in student performance. The progressive increase in students’ mastery and metacognitive accuracy suggests that integrating structured self-assessment into formative testing supports learning achievement and reflective awareness. This study implies that SLOA-based formative tests can serve as a strategic framework to foster student independence, provided that they are implemented with adequate instructional time and systematic feedback cycles.